Communication Strategy of Personal Branding of Instagram Celebrities in Building Credibility on Social Media - Dika, Dika; Sonni, Alem Febri; Sukmarini, Andi Vita (Journal La Sociale, 2023)
This study aims to Describe the Personal Branding Communication strategy of Celebrity Rijal Djamal on Instagram social media. This study was conducted by observing the Instagram social media @Rijalsystem. Data collection was carried out through in-depth interviews, observation, and documentation, using qualitative methods with a descriptive qualitative approach. The results of this study indicate that the form of Rijal Djamal's Personal branding in his Instagram social media account @Rijalsystem has fulfilled the eight concepts of Personal branding according to Peter Montoyo, namely the first specialization, the form of specialization that Rijal Djamal emphasizes on his expertise in Content Creator and Public Speaking, the second leadership, Rijal Djamal shows himself as a figure who cares about the needs of his Followers in this case Rijal Djamal often shares educational posts such as sharing motivational posts in learning Public Speaking, the third personality, Rijal Djamal displays a Humanist, Humble, and communicative person. The fourth characteristic, building a competent personality, the fifth visibility, consistent and patterned from every content or photo shared on social media is always related to the tasks or achievements achieved. The sixth unity, Rijal Djamal forms his Personal branding in harmony or relevant to his personal life. Seventh, steadfastness, Rijal Djamal has consistently posted content from 2019, one content at a time, and eighth, good intentions, good intentions built by Rijal Djamal such as giving positive responses or appreciating through Instagram posts of people who are learning Public Speaking.